COGNITIVE RESTRUCTURING SEBAGAI STRATEGI MENINGKATKAN FOKUS, REGULASI EMOSI, DAN MENTAL JUARA ATLET - Nova Elisa; Septia Anggraini; Amalina Diananda Safira; Aisya Briliana Putri K; Ari Khusumadewi; Devi Ratnasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines the role of Cognitive Restructuring as an effective psychological strategy for improving focus, emotional regulation, and developing a champion mentality in athletes. Using a literature review method, this research examines various scientific findings related to the implementation of Cognitive Restructuring in the context of competitive sports. The results indicate that cognitive restructuring helps athletes identify and transform negative, irrational, and unproductive thoughts into more adaptive, realistic, and empowering thought patterns. This process contributes to improved concentration, anxiety management, emotional stability, and strengthened motivation and self-efficacy. Furthermore, this technique strengthens athletes' mental readiness to face competitive pressure, performance demands, and the dynamics of the sporting environment. Thus, Cognitive Restructuring can be a sustainable intervention in developing a champion mentality while supporting optimal athlete performance across various sports.